(untitled) (Revista de Biología Marina y Oceanografía, 2021)
There are abundant reports of symbiosis wherein crustaceans live inside or on mollusks; however, there are few published records of gastropods hosting decapods. This study examines the biological association between fifteen snails (124.86 ± 19.01) from the species Pacific crown conch Melongena patula and the porcelain crab Euceramus transversilineatus. Morphometric relationships of both invertebrates, as well as some sexual characteristics of the crab were conducted. These invertebrates were sampled in the Navachiste Lagoon, in the south eastern Gulf of California, Sinaloa, Mexico. It was found 86.6% of the snails housed at least a female or a male porcelain crab (17.82 ± 3.27 mm total body length) or a pair of them (heterosexual and same sex) with a sexual proportion of 2M:1F. There were no correlations between any of the crab and snail based on their analyzed morphometric relationships. For the crab males, the measurements of both chelae presented relationships with total body length, carapace length, and abdomen width however, no significant differences were observed between the mean width and chelae length of males, females or between sexes. Of the six females collected, four were gravid. Preliminary observations indicated that the porcelain crab E. transversilineatus is a commensal endosymbiont that coexist in short-term association with M. patula. Their population distribution suggests that E. transversilineatus are polygamous with a promiscuous mating pattern.